2001
DOI: 10.1080/010503901300006985
|View full text |Cite
|
Sign up to set email alerts
|

Progression of sensorineural hearing impairment in aided and unaided ears

Abstract: To cite this article: Tapani Jauhiainen (2001) Progression of sensorineural hearing impairment in aided and unaided ears, Scandinavian Audiology, 30:1, 28-31To link to this article: http://dx.The possibility of "adult onset auditory deprivation" has been proposed as a condition of extensive deterioration of speech discrimination in unaided ears. Pure tone thresholds and speech discrimination were studied in a follow-up examination on 500 patients using hearing aids unilaterally. The follow-up time ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
1
Order By: Relevance
“…Although there can be some recovery from deprivation, there are also cases known where the auditory deprivation effect is not reversible (Gelfand, 1995). In contrast to other investigators, Jauhiainen (2001) found no indications for the onset of auditory deprivation in unaided ears.…”
Section: Reasons For Choosing Bilateralcontrasting
confidence: 99%
“…Although there can be some recovery from deprivation, there are also cases known where the auditory deprivation effect is not reversible (Gelfand, 1995). In contrast to other investigators, Jauhiainen (2001) found no indications for the onset of auditory deprivation in unaided ears.…”
Section: Reasons For Choosing Bilateralcontrasting
confidence: 99%